Cell stemness, epithelial-to-mesenchymal transition, and immunoevasion: Intertwined aspects in cancer metastasis. (February 2020) - Romano, Simona; Tufano, Martina; D'Arrigo, Paolo; Vigorito, Vincenza; Russo, Salvatore; Romano, Maria Fiammetta
Abstract: Recent advances in tumor immunology, fostered by dramatic outcomes with cancer immunotherapy, have opened new scenarios in cancer metastasis. The cancer stemness/mesenchymal phenotype and an excess of immune suppressive signals are emerging as Intertwined aspects of human tumors. This review examines recent studies that explored the mechanistic links between cancer cell stemness and immunoevasion, and the evidence points to these key events in cancer metastasis as two sides of the same coin. This review also covers the mechanisms involved in tumor expression of programmed cell death ligand 1 (PD-L1), a major factor exploited by human neoplasias to suppress immune control. We highlight the convergence of mesenchymal traits and PD-L1 expression and examine the functions of this immune inhibitory molecule, which confers cancer cell resistance and aggressiveness.